Repository Development Based on the Archive Initiative Protocol for Metadata Harvesting (OAI-PMH) on METS and MPEG-21 DIDL - Taufiq Iqbal, Syarifuddin (International Journal of Advanced Science and Technology, 2020)
This study aims to build a repository that can be used as a form of publication and publication management and features the Archives Initiative Protocol for Metadata Harvesting (OAI-PMH) and the Metadata Encoding and Transmission Standard (METS) and MPEG-21 Digital Item Declaration Language (DIDL). so that it can properly handle indexed metadata and sharing from various online digital sources. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. In the software development model using the Waterfall model until the final stage, testing is carried out by verifying the validation of OAR compliance with the OAI-PMH built. The developed repository can help educational institutions as an alternative in providing a repository for educational institutions in Indonesia.